Relationship between Knowledge Level and Incidence of Skin Diseases: Hubungan Tingkat Pengetahuan Terhadap Kejadian Penyakit Kulit - Prasetya, Didik; Abadi, Moh Fairuz (Universitas Muhammadiyah Sidoarjo, 2025)
Onychomycosis is a fungal infection of the nail frequently found in tropical regions and may negatively impact community health and quality of life. This study aimed to examine the association between public knowledge and the incidence of onychomycosis in Banjar Dinas Batang, Karangasem Regency. An analytical observational design with a cross-sectional approach was employed. A total of 30 adults were selected using purposive sampling based on inclusion criteria. Knowledge levels were assessed using a closed-ended questionnaire, and laboratory diagnosis was confirmed through culture on Sabouraud Dextrose Agar and microscopic observation with Lactophenol Cotton Blue staining. The results revealed that 60% of participants had nail fungal infections, most commonly in those with low knowledge levels (66.7%). Statistical analysis showed a significant association between knowledge and infection incidence (p = 0.045; PR = 4.25). Identified fungal species included Aspergillus spp., Zygomycetes, and yeasts. These findings suggest that limited knowledge increases the risk of onychomycosis. Community-based health education is essential to promote preventive behavior, especially in moist environments that favor fungal growth.